2017
DOI: 10.1002/cplu.201700085
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric and Vibrational Characterization of Reaction Intermediates in [Ru(bpy)(tpy)(H2O)]2+ Catalyzed Water Oxidation

Abstract: Mass spectrometry coupled with an in-line electrochemical electrospray ionization source is used to capture some of the reactioni ntermediates formed in the [Ru(bpy)(tpy)(H 2 O)] 2 + (bpy = 2,2'-bipyridine, tpy = 2,2':6',2"-terpyridine) catalyzed water oxidation reaction. By controlling the appliede lectrochemicalp otential, we identified the parentc omplex, as well as the first two oxidation complexes, identifieda s[ Ru(bpy)-(tpy)(OH)] 2 + and [Ru(bpy)(tpy)(O)] 2 + .T he structures of the parenta nd first oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The vibrational spectra of the [ Ru (OH)] 2+ (H 2 O) n clusters with n = 0–4 were acquired using a dual cryogenic ion trap infrared predissociation mass spectrometer described in detail previously . The [ Ru (OH)] 2+ intermediate species was generated using an in-line electrochemical–electrospray (EC–ESI) setup, similar to those of Johnson and van Berkel, and described previously . Briefly, a millimolar solution of [ Ru (H 2 O)]­(ClO 4 ) 2 in water was pushed through an electrochemical flow cell equipped with a glassy carbon working electrode held at 1.2 V with respect to a stainless steel counter electrode.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vibrational spectra of the [ Ru (OH)] 2+ (H 2 O) n clusters with n = 0–4 were acquired using a dual cryogenic ion trap infrared predissociation mass spectrometer described in detail previously . The [ Ru (OH)] 2+ intermediate species was generated using an in-line electrochemical–electrospray (EC–ESI) setup, similar to those of Johnson and van Berkel, and described previously . Briefly, a millimolar solution of [ Ru (H 2 O)]­(ClO 4 ) 2 in water was pushed through an electrochemical flow cell equipped with a glassy carbon working electrode held at 1.2 V with respect to a stainless steel counter electrode.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Specifically, we probed the effect of solvation on the OH bond lengths at the active site of the catalyst via a stepwise addition of water molecules to the isolated catalyst ion . We also showed that the product of the first oxidation step, the open-shell [ Ru (OH)] 2+ complex, can be isolated and characterized utilizing an in-line electrochemical cell with the electrospray source …”
Section: Introductionmentioning
confidence: 99%
“…Bands at 1571, 1722, 1217, 1108 cm −1 in the infrared spectrum of SWCNT‐tpyRubpy (Figure 4a) are attributed to C═C stretching vibration, C–OH stretching vibration, C–O stretching vibration, C–O stretching vibrations of the carbon nanotube structure, [ 41 ] respectively, and the vibration bands between 700–1500 cm −1 can be assigned to ligands of terpyridine and bipyridine. [ 42 ] The presence of these bands indicate the successful incorporation of tpyRubpy in SWCNTs.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to isolate some of the more stable intermediates in the catalytic cycle using an electrochemical flow cell coupled to an ESI source . However, no [ Ru (O 2 )] 2+ complex could be isolated even with such a source.…”
Section: Accessing Reactive Intermediatesmentioning
confidence: 99%
“…59 We were able to isolate some of the more stable intermediates in the catalytic cycle using an electrochemical flow cell coupled to an ESI source. 60 However, no [Ru(O 2 )] 2+ complex could be isolated even with such a source. We thus set out to form the [Ru(O 2 )] 2+ complex using the reaction trap via the reverse reaction, i.e., O 2 + [Ru] 2+ → [Ru(O 2 )] 2+ .…”
Section: Accessing Reactive Intermediatesmentioning
confidence: 99%